Epistasis studies reveal redundancy among calcium-dependent protein kinases in motility and invasion of malaria parasites - Hanwei Fang; Ana Rita Gomes; Natacha Klages; Paco Pino; Bohumil Maco; Eloise M. Walker; Zenon A. Zenonos; Fiona Angrisano; Jake Baum; Christian Doerig; David A. Baker; Oliver Billker; et al. (Nature Communications, 2018)
Despite functional optimisation during evolution of parasitism, most members of a calcium dependent protein kinase (CDPK) family show genetic redundancy in Plasmodium. Here, the authors screen 294 genetic interactions among protein kinases in Plasmodium and show how some CDPKs functionally interact to control motility and host cell invasion.